Growth issues in developing countries: an overview - Fuentes, Rodrigo (Estudios de Economía, 2016)
This brief overview highlights some of the most relevant aspects addressed in the different papers, concerning a wide range of countries in the world, in this especial issue devoted to economic growth. All papers have a common core: how economic policy affects growth, especially emphasizing the determinants of productivity growth and the relation between international trade and growth.